Phase Transition in Cu2+-Doped RbH2PO4 as Observed by EPR - Demir, D.; Köksal, F.; Köseoǧlu, R. (Taylor & Francis Ltd, 2009)
The electron paramagnetic resonance (EPR) spectra of Cu2+-doped RbH2 PO4 at elevated temperatures indicate a phase transition at 358K. The EPR-silent state at this temperature is attributed to a so-called polymeric phase transition. After the transition when the temperature is lowered to 293K, the EPR signal does not appear; therefore, the transition is irreversible. This result seems to be in agreement with the other observations. The EPR spectra for the sample indicate the presence of two sites for Cu2+, and the values of EPR parameters are in accord with the literature on Cu2+-doped single crystals. Any other phase transitions could not to be observed at low temperatures down to 113K.
Keywords: Cu2+ Doping; EPR; Phase Transition; RbH2 PO4